DFA Analysis Revolutionizes FSAE Steering, Enhancing Efficiency in Automotive Design: Analisis DFA Merevolusi Kemudi FSAE, Meningkatkan Efisiensi dalam Desain Otomotif - Kurniawan, Mukhammad Isa; Mulyadi (Universitas Muhammadiyah Sidoarjo, 2024)
In the dynamic realm of automotive engineering, particularly in Formula Society of Automotive Engineers (FSAE) racing, where vehicle assessment is based on efficiency, motor power, chassis dynamics, and steering, there exists a notable focus on steering system design. This research delves into the conceptualization and component development aimed at aiding automotive mechanics in crafting steering systems for FSAE race cars. Employing Solid Edge 2021 software, the study utilizes the Design of Assembly (DFA) analysis method to streamline the mechanical process. Through DFA analysis, the study assesses various Technical Attributes (TAs) of the steering system, revealing values ranging from 0.548 to 1.765. The ideal steering system ensures that the desired steering input by the driver aligns with the output motion of the vehicle, known as the Ackerman condition. Steering gear mechanisms translate rotational motion into translation and adjust the effort applied to the steering linkage. The study's findings contribute to the advancement of steering system design in FSAE vehicles, emphasizing ergonomic considerations and the utilization of advanced software tools like Catia and Solid Edge 2021 for enhanced performance and safety. Highlight: FSAE steering: DFA analysis enhances design efficiency for racing vehicles. Software aid: Solid Edge 2021 streamlines FSAE steering system development. Ergonomic focus: Design prioritizes driver comfort and vehicle performance optimization. Keywoard: FSAE vehicles, Steering system design, DFA analysis, Solid Edge 2021, Ergonomics